Tracking two invasions for the cost of one: opportunistically tracking the range expansion of non-native Palaemon macrodactylus in the Salish Sea through participatory science - Grason, Emily W.; Pineda, Jessica; McDonald, P. Sean (Frontiers in Marine Science, 2025)
While conducting early detection monitoring for invasive European green crab (Carcinus maenas), Washington Sea Grant Crab Team discovered a non-native shrimp Palaemon macrodactylus, hitherto unreported along Washington’s portion of the Salish Sea. By examining prior data, and tracking this species closely over subsequent years, we were able to consistently monitor the spread and increase of this species across the region. The program and dataset enabled a highly quality-controlled and verified record of this species. Originating near the Canadian border, P. macrodactylus has spread southward into the main basins of Puget Sound and has been observed in Hood Canal as well. At sites where this shrimp has been consistently documented, the relative abundance over time has increased, indicating that the invasion has become established but not yet reached equilibrium. Similar to studies in other regions of the globe where it is found, we observed that P. macrodactylus favors estuarine habitats and demonstrates seasonal migration within creek systems. The Salish Sea population is within demographic values published for other invasions, but females achieve a smaller maximum size, and reproductive maturity at a smaller size than those reported from the native range. This might suggest the potential for an altered life history strategy favored by introduction to a novel evolutionary context. Given the rate of spread over the last decade, and density of suitable habitat, we anticipate that P. macrodactylus will continue to expand its range within the Salish Sea. No ecological impacts of this species have been documented elsewhere. Nevertheless, this approach demonstrates the benefit of participatory science monitoring in tracking cryptic or otherwise unnoticed species invasions.